2013
DOI: 10.1371/journal.pone.0081213
|View full text |Cite|
|
Sign up to set email alerts
|

Association of pol Diversity with Antiretroviral Treatment Outcomes among HIV-Infected African Children

Abstract: BackgroundIn HIV-infected children, viral diversity tends to increase with age in the absence of antiretroviral treatment (ART). We measured HIV diversity in African children (ages 6–36 months) enrolled in a randomized clinical trial comparing two ART regimens (Cohort I of the P1060 trial). Children in this cohort were exposed to single dose nevirapine (sdNVP) at birth.MethodsHIV diversity was measured retrospectively using a high resolution melting (HRM) diversity assay. Samples were obtained from 139 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 43 publications
2
12
1
Order By: Relevance
“…There was no association between HIV diversity and viral load among men who were HIV infected at study enrollment, and lower HIV gag diversity was only weakly associated with higher CD4 cell count after adjusting for other factors. These findings are consistent with other studies that reported no association of HIV diversity with viral load [13,20,21] or CD4 cell count [11,17]. We did find that HIV pol diversified more over 12 months among men who had higher CD4 cell counts and lower HIV viral loads at study enrollment.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…There was no association between HIV diversity and viral load among men who were HIV infected at study enrollment, and lower HIV gag diversity was only weakly associated with higher CD4 cell count after adjusting for other factors. These findings are consistent with other studies that reported no association of HIV diversity with viral load [13,20,21] or CD4 cell count [11,17]. We did find that HIV pol diversified more over 12 months among men who had higher CD4 cell counts and lower HIV viral loads at study enrollment.…”
Section: Discussionsupporting
confidence: 92%
“…Prolonged exposure to non-suppressive ART has been significantly associated with decreases in HIV diversity in pol in adults [32] and in gag , pol , and env in children [19]. Lower gag diversity was also associated with self-reported prior maternal ARV drug use in a cohort of African children [20]. These findings suggest that the selective pressure exerted by ARV drugs may influence HIV diversity in regions other than pol .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, the survival strains may present drug resistance mutations [ 33 ] that often increase genetic diversity of the protein-coding genes of the target proteins [ 12 , 34 , 35 ]. Wu et al [ 36 ] found that patients treated with several PIs presented 3 times more protease mutations than untreated patients.…”
Section: Genetic Diversity Generated During Hiv-1 Antiviral Therapmentioning
confidence: 99%